Hand Allotransplantation - Brandacher, Gerald (Thieme Medical Publishers, 2010)
In the past decade, more than 100 different composite tissue allotransplantation (CTA) procedures have been performed around the world including more than 50 hand and 8 facial transplants with encouraging graft survival and excellent functional outcomes. Broader clinical application of CTA, however, continues to be hampered by requirement for long-term, high-dose, multidrug maintenance immunosuppression to prevent graft rejection mediated particularly by composite tissue allograft's highly immunogenic skin component. Medication toxicity could result in severe adverse events including metabolic and infectious complications or malignancy. Notably, unlike in solid organs, clinical success is dictated not only by graft acceptance and survival but also by nerve regeneration, which determines ultimate functional outcomes. Novel strategies such as cellular and biologic therapies that integrate the concepts of immune regulation with those of nerve regeneration have shown promising results in small and large animal models. Clinical translation of these insights to reconstructive transplantation and CTA could further minimize the need of immunosuppression and optimize functional outcomes. This will enable wider application of such treatment options for patients in need of complex reconstructive surgery for congenital deformities or devastating injuries that are not amenable to standard methods of repair.